Croconaine‐Based Polymer Particles as Contrast Agents for Photoacoustic Imaging. Issue 22 (12th October 2020) - Jansen, Felicitas; Lamla, Markus; Mauthe, Diana; Fischer, Stephan; Barth, Holger; Kuehne, Alexander J. C.
Abstract: In the development and optimization of imaging methods, photoacoustic imaging (PAI) has become a powerful tool for preclinical biomedical diagnosis and detection of cancer. PAI probes can improve contrast and help identify pathogenic tissue. Such contrast agents must meet several requirements: they need to be biocompatible, and absorb strongly in the near‐infrared (NIR) range, while relaxing the photoexcited state thermally and not radiatively. In this work, polymer nanoparticles are produced with croconaine as a monomer unit. Small molecular croconaine dyes are known to act as efficient pigments, which do not show photoluminescence. Here, for the first time croconaine copolymer nanoparticles are produced from croconic acid and a range of aromatic diamines. Following a dispersion polymerization protocol, this approach yields monodisperse particles of adjustable size. All synthesized polymers exhibit broad absorption within the NIR spectrum and therefore represent suitable candidates as contrast agents for PAI. The optical properties of these polymer particles are discussed with respect to the relation between particle size and outstanding photoacoustic performance. Biocompatibility of the polymer particles is demonstrated in cell viability experiments. Abstract : Monodisperse polymer particles based on croconaine dyes with tunable size are synthesized via dispersion polymerization. These particles function as organic near‐infrared absorbers. A superior photoacoustic activity in combination with good cell viability studies shows that these particles have high potential for use in biomedical imaging applications.